Screening practices for cervical and breast cáncer in Costa Rica - Irwin, Kathleen L. (1991)
Cervical cancer and breast cancer are leading causes of cancer-related morbidity and mortality in Costa Rica. This article reports results of an evaluation of cervical and breast cancer screening practices among Costa Rican women 25 to 58 years old that was based on a nationwide 1984-1985 survey. The evaluation showed that while Pap smears were widely used to screen for cervical cancer, many women did not have their first cervical smear or gynecologic examination until age 30, and that cervical cancer screening was less common among certain high-risk groups, including women with multiple sexual partners and those with high parity. Less than half the women surveyed reported having had a breast examination by a health care provider. Utilization of both cervical cancer and breast cancer screening examinations could be increased by targeting inadequately screened high-risk women through the existing health care system